PROGRAM-TARGET MANAGEMENT IN THE FORMATION OF REGIONAL INSTITUTIONS OF ECONOMIC DEVELOPMENT - Ekaterina Milovanova (Вестник Северо-Кавказского федерального университета, 2022)
The main mechanisms of balancing revenues and expenditures of the consolidated budget of the Russian Federation in accordance with the planned targets is to use the tools of program management in the framework of the state development programmes. The results of the evaluation of the effectiveness of existing control software showed that the required optimization due to precise definition of development priorities, reducing the number of duplicate programs, the creation of a unified socio-economic space at the hierarchical levels of the fiscal system.